EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK TALKING CHIPS DALAM MENINGKATKAN PENYESUAIAN DIRI SISWA TERHADAP PEMBELAJARAN DARING DI SMA TEUKU UMAR SEMARANG - Putri, Riska Yunita (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
This research is motivated by students who experience low self-adjustment caused by factors that students have difficulty adapting to at school, and students often lack self-confidence. The research was conducted at Teuku Umar Senior High School Semarang. The study population was 106, the sample was taken from class XI IPS 2 with a total of 36 students and 8 students participated in group guidance services. The sample was obtained from the Porposive Sampling Technique. The aim is to find out the low self-adjustment of students through group guidance services using the talking chips technique. This type of research is experimental using pre-experimental with one group pre-test post-test design. The results of the questionnaire analysis of the percentage of Pre Test (77.375%) are in the low category, then the results of the Post Test (156.875 %) are included in the very high category, with an increasing percentage (0.745%). Then based on the results of the Wilxocon test, it is known that Asymp. Sig. (2-tailed) is 0.012. The value of 0.012 is smaller than < 0.05. So it can be concluded that "the hypothesis is accepted". This means that there is a difference between the results of students' self-adjustment development after being given treatment with group guidance with the talking chips technique on the self-adjustment of students in class XI IPS 2 at SMA Teuku Umar Semarang.